Criminology of atrocity crimes from a macro-, meso- and micro-level perspective - Odriozola-Gurrutxaga, Miren (International e-journal of criminal sciences, 2015)
The present article looks at the aetiology of atrocity crimes. Theories which focus on one level of analysis cannot fully explain such a criminal phenomenon. Thus, the author studies the factors which are involved in the aetiology of mass atrocity at three different levels: macro (international and national), meso (group) and micro (individual) level. Notwithstanding the heterogeneity of the conducts which lead to atrocity crimes, the perpetrators of such crimes can be grouped into three main categories: top-, mid- and low-level perpetrators. The final aim of analysing the dynamics of mass atrocity from a macro-, meso- and micro-level perspective lies in describing the role that the members pertaining to each category usually play in the perpetration of such heinous crimes.